2018
DOI: 10.1038/s41598-018-26823-5
|View full text |Cite
|
Sign up to set email alerts
|

Healthy lifestyle behaviors and control of hypertension among adult hypertensive patients

Abstract: The aim of the present study was to evaluate the healthy lifestyle behaviors in hypertensive patients (aware, n = 1364 and not aware, n = 1213) based on 2011 national survey of risk factors of non-communicable disease (SuRFNCD) of Iran. Lifestyle score was calculated based on lifestyle behaviors, including smoking status, nutrition, physical activity status and body mass index separately for each patient. Of all aware patients, 27.79% (22.35–33.64) were adherence to the good lifestyle category. Almost the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
4
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 35 publications
1
28
4
6
Order By: Relevance
“…The prevalence of smoking in this study was 3.3% with 95% CI (2.05%, 5.38%). this nding was lower than a study done at Durame (16) which was 8.8%, Hiwot Fana (26) which was 18.5%, India (32) which was 11%, Kenya which was 8.3% (33) different part of Nigeria which was 15.4% and 12.2% (34,35) Canada which was 22% (36),Korea which was 34.2% (37),Iran which was 15.3% (38). Also, the prevalence of alcohol consumption in this study was 9.8% with 95% CI (7.42%, 12.80%).…”
Section: Discussioncontrasting
confidence: 55%
“…The prevalence of smoking in this study was 3.3% with 95% CI (2.05%, 5.38%). this nding was lower than a study done at Durame (16) which was 8.8%, Hiwot Fana (26) which was 18.5%, India (32) which was 11%, Kenya which was 8.3% (33) different part of Nigeria which was 15.4% and 12.2% (34,35) Canada which was 22% (36),Korea which was 34.2% (37),Iran which was 15.3% (38). Also, the prevalence of alcohol consumption in this study was 9.8% with 95% CI (7.42%, 12.80%).…”
Section: Discussioncontrasting
confidence: 55%
“…According to Perl et al [29], ensuring that patients receive appropriate education improves adherence to lifestyle interventions. Moreover, Akbarpour et al [30] states adherence to a good lifestyle is significantly higher among patients who are aware of the status of their condition. Therefore, a system that gives feedback, creates awareness, and recommends lifestyle behavior change can contribute significantly to a satisfactory control of blood pressure [31]- [33].…”
Section: Introductionmentioning
confidence: 99%
“…The results underscored the importance of lifestyle behaviors in the management of CKD. Supporting evidence revealed that lifestyle behaviors had complicated associations with the risks of hypertension [22], CVD (stroke and heart failure) [23], metabolic syndrome [24], cancer [25], T2DM [26], and CKD with T2DM [27]. As we all know, diabetes, hypertension and obesity are important traditional risk factors for CKD [28].…”
Section: Discussionmentioning
confidence: 99%